Fraud prevention through financial management accountability: The role of amanah-based governance and employee competence in the ministry of religious affairs - Elex Sarmigi; Endah Sri Wahyuni; Alek Wissalam Bustami; Mursal Mursal (Indonesia Accounting Research Journal, 2026)
This study investigates the roles of amanah-based governance and employee competence in preventing fraud through financial management accountability within the Ministry of Religious Affairs in Jambi Province, Indonesia. Guided by the Fraud Hexagon Theory, the study examines how ethical values, technical skills, and accountability mechanisms interact to reduce the risk of fraudulent behavior in public sector financial management. Data were collected from 200 employees of the ministry and analyzed using Structural Equation Modeling (SEM) to assess the direct and indirect effects of governance and competence on fraud prevention. The findings indicate that while amanah-based governance provides a moral foundation and shapes ethical awareness, it does not directly enhance accountability or prevent fraud. In contrast, employee competence has a significant direct impact on both financial management accountability and fraud prevention. Financial management accountability strengthens fraud prevention by providing structural mechanisms to limit opportunities for misconduct, though it does not significantly mediate the effects of ethical governance or employee competence. These findings suggest that public sector organizations should complement ethical governance values with systematic capacity-building programs, professional training in financial management, and stronger accountability mechanisms. For government institutions, particularly the Ministry of Religious Affairs, strengthening employee competence and implementing transparent financial management systems are essential to translate ethical principles into effective fraud prevention practices. Overall, the results highlight the importance of integrating ethical governance, skilled personnel, and robust accountability systems to operationalize moral principles and mitigate fraud risks effectively.